The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/jcm11020361
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Acromial and Scapular Spine Strain after Reverse Total Shoulder Arthroplasty: A Systematic Review of Biomechanical Studies

Alexander Paszicsnyek,
Olivia Jo,
Harshi Sandeepa Rupasinghe
et al.

Abstract: Background: Acromial and scapular spine fractures after reverse total shoulder arthroplasty (RTSA) can be devastating complications leading to substantial functional impairments. The purpose of this study was to review factors associated with increased acromial and scapular spine strain after RTSA from a biomechanical standpoint. Methods: A systematic review of the literature was conducted based on PRISMA guidelines. PubMed, Embase, OVID Medline, and CENTRAL databases were searched and strict inclusion and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
10
0
2
Order By: Relevance
“…The rate of post-RTSA acromial fracture (2.2%) in both the study group and the control group was lower than the rates reported in the most recent literature (3.7%-10%). 5 , 11 , 12 However, the cited studies were able to evaluate larger populations of patients undergoing RTSA compared with our study. 11 , 12 Prior studies have evaluated patient factors and sequelae of operative techniques that predispose patients to acromial fractures after RTSA.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The rate of post-RTSA acromial fracture (2.2%) in both the study group and the control group was lower than the rates reported in the most recent literature (3.7%-10%). 5 , 11 , 12 However, the cited studies were able to evaluate larger populations of patients undergoing RTSA compared with our study. 11 , 12 Prior studies have evaluated patient factors and sequelae of operative techniques that predispose patients to acromial fractures after RTSA.…”
Section: Discussionmentioning
confidence: 79%
“…The incidence of acromial and scapular spine stress fractures after RTSA has been reported as up to 10%. 5 Preoperative patient factors including female sex, osteoporosis, and acromial anatomy, as well as the biomechanical changes and excess stress placed on the acromion inherent to RTSA, have been identified as risk factors. 5 …”
mentioning
confidence: 99%
“…Although we were unable to determine the fixation construct with the best clinical performance, our study of pooled results suggests that using a single locking plating for lateral acromion and acromial base fractures (Levy Type I and II), and a dual plating construct for more medial fractures (Levy Type II and III) delivers a high union rate and a reasonably low complication rate. Together with the current biomechanical knowledge about acromion and scapular spine fractures following RSA [ 5 ] and plating techniques [ 35 ], it seems that dual plating reveals a stronger fixation construct than single plating and may yield superior outcomes in more medial fractures, although the latter is yet to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…Several RSA-specific factors influence acromial/scapular spine strain, with glenoid lateralization being one of the main factors leading to increased strain [ 5 ]. Thus the growing trend towards increased lateralization of the center of rotation (COR) may exacerbate the difficult problem of acromion or scapular spine fractures following RSA [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found significantly increased strain in all Levy zones at 0° flexion when glenoid lateralization was increased from 0 to +10 mm. Furthermore, a systematic review by Paszicsnyek et al 50 that included 6 studies with 36 cadavers and 11 CT reconstructions concluded that there was a linear relationship between increased glenoid lateralization and increased acromion and SS strain based on 4 included studies demonstrating a positive relationship 45,47,51,52 . However, the influence of glenoid lateralization is likely dependent on humeral lateralization; Shah et al 47 found that cases with greater humeral onlay (+10 or +13 mm) demonstrated a significant increase in acromial strain when lateralizing the glenoid from 0 to +6 mm.…”
Section: Modifiable Surgical Factorsmentioning
confidence: 99%